(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In Central Asia, asceticism emerged in the 8th–9th centuries as an independent ideological-social movement, occupying a significant place in the region’s religious, scholarly, and social life. In this article highlights of the ascetic movement in central Asia during the 8th-9th centuries: religious and social processes.